Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian pada Kentucky Fried Chicken (KFC) Kota Probolinggo - Fadia Febriani Wijaya; Ngatimun Ngatimun; Agung Yatiningrum (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The decision to purchase KFC in Probolinggo City can be maximized if the conditions are met properly. One factor in improving product quality is by providing good product quality and prices that match the quality of the products being marketed. This research aims to determine the influence of product quality and price on partial purchasing decisions at KFC Probolinggo City. This research method is quantitative with a causal associative approach. The population of this research is consumers who made purchases at KFC Probolinggo City in February 2022, totaling 719 consumers. The sampling technique used non-probability sampling, namely accidental sampling. The sample in this research was 75 respondents. The data sources used in this research came from primary data and data secondary. Data was collected through questionnaires and completed through data analysis methods in the form of validity tests, reliability tests, classical assumption tests, multiple regression analysis, coefficient of determination (R-Square) and hypothesis testing. The results of the research show that partial product quality has no significant effect on Purchasing decisions and price partially have a significant effect on purchasing decisions.